A Novel Approach of Improving Battery Performance and Longevity of the Developed Electrically Assisted Triwheeler Vehicle by Implementing Torque Sensor Technology. (17th July 2017) - Rashid, Md. Jaber Al; Rahman, Ataur; Siddique, Abu Raihan Mohammad; Azad, A. K. M. Abdul Malek
Abstract : This paper presents a new approach to improving the battery performance and its longevity by the implementation of torque sensor pedal technology on the developed electric triwheeler vehicle (i.e., wheelchair). The paper has also discussed integration of the torque sensor technology with the overall electrical system of the vehicle. Incorporating the components of torque sensor technology reduces the human effort immensely by providing assistance from the battery bank to drive a hub motor while maneuvering the wheelchair using the torque sensor pedal. Field tests were carried out in three different stages, one with pedal, one with the throttle only, and with varying the load on the wheelchair, to distinguish the effect of load test on battery performance using the pedal. Results of the field tests reveal that the state of charge of batteries has been minimized using the pedal due to the contribution of the muscular energy of the user along with the battery energy to meet the total energy demand of the motor. Analyzing test results with the torque sensor pedal clarifies that the vehicle covers a longer distance, lessens power dissipation from the batteries, and reduces energy consumption from the batteries, which leads to improvement of the battery performance and its longevity ensuring sustainability of the electric vehicle.